Impact of the COVID-19 pandemic on functional urology practice: A nationwide survey from Turkey COVID-19 pandemisinin fonksiyonel üroloji uygulamasına etkisi: Türkiye çapında bir araştırma - ONUR, AHMET RAHMİ (My University, 2022)
© 2022, Galenos Publishing House. All rights reserved.Objective: Routine urology practice has changed with the coronavirus disease-2019 pandemic. We aim to determine the urologists’ functional urology practice during the pandemic by an online questionnaire. Methods: An online questionnaire was conducted to assess the functional urology practice of Turkish urologists’ during the pandemic. The workplace, positioning as a pandemic hospital, involvement in pandemic clinics, and the relevance to functional urology were questioned. We also inquired about outpatient services, diagnostic tests, and elective surgeries during the pandemic compared with their routine practice. Results: One hundred and fifty-two participants completed the questionnaire. Of these, 32.2% replied that more than half of their daily practice was related to diagnosing and treating incontinence, prolapse, and neurourology. According to 123 participants (80.9%), there was a decrease in outpatient clinics. Diagnostic tests were also reduced, such as uroflowmetry (68.4%) and urodynamics (81.3%). The majority of respondents declared a decrease in elective surgeries as Botox injection (92.1%), surgery for urinary incontinence (93.4%), and surgery for prolapse (85%). Nearly one-quarter of respondents’ (28.9%) stated that their diagnostic methods for neurourology patients did not differ. Conclusions: One of the most affected areas in urology during a pandemic is functional urology. Although diagnostic tests and surgery for functional urology are classified as \"optional,\" the quality of life of patients will be affected by the delayed intervention.

Amaç: Koronavirüs hastalığı-2019 pandemisi ile rutin üroloji pratiği değişmiştir. Bu çalışmada pandemi sırasında ürologların fonksiyonel üroloji uygulamalarını çevrimiçi bir anket kullanarak belirlemek amaçlanmıştır. Yöntemler: Türk ürologlarının pandemi sırasında fonksiyonel üroloji pratiğini değerlendirmek için çevrimiçi bir anket uygulandı. Bu ankette, katılımcıların görev yeri, pandemi merkezi olarak konumlandırılması, pandemi kliniklerinde görev alma ve fonksiyonel ürolojiye ilgi hakkında sorular soruldu. Ayrıca pandemi sırasında poliklinik hizmetleri, tanı testleri ve elektif ameliyatlar, pandemi öncesi günlük uygulamalarıyla karşılaştırarak sorgulandı. Bulgular: Toplam 152 katılımcı anketi tamamladı. Katılımcıların %32,2’si günlük uygulamalarının yüzde ellisinden fazlasının inkontinans, prolapsus ve nöroüroloji tanı ve tedavisi ile ilgili olduğunu belirtti. Yüz yirmi üç katılımcıya (%80,9) göre poliklinik sayısında azalma oldu. Üroflovmetri (%68,4) ve ürodinami (%81,3) gibi tanı testleri de azaldı. Ankete katılanların çoğunluğu, botoks enjeksiyonu (%92,1), üriner inkontinans cerrahisi (%93,4) ve prolapsus cerrahisi (%85) gibi elektif ameliyatlarda azalma olduğunu bildirdi. Ankete katılanların yaklaşık dörtte biri (%28,9) nöroüroloji hastaları için tanı yöntemlerinin farklılık göstermediğini belirtti. Sonuçlar: Pandemi sırasında ürolojide en çok etkilenen alanlardan biri fonksiyonel ürolojidir. Fonksiyonel ürolojiye yönelik testler ve ameliyatlar “opsiyonel” olarak sınıflandırılsa da hastaların yaşam kalitesi geciken müdahalelerden etkilenecektir.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; Klinik Tıp (MED); Klinik Tıp; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICINE, GENERAL & INTERNAL; Genel Tıp; General Medicine; Coronavirus; COVID-19; functional urology; neurourology; Coronavirus; COVID-19; functional urology; neurourology; Koronavirüs; COVID-19; fonksiyonel üroloji; nöroüroloji